Rural wetlands use and sustainability: a case study of Zindi area in Honde Valley, Zimbabwe - Mandishona, Emmah (My University, 2021)
Wetlands are crucial as they provide different ecosystem services that support livelihoods. However, uncontrolled use of wetlands globally has compromised wetland sustainability and negatively impacted on people and the natural environment. The thrust of this qualitative study is to understand how people in Zindi rural area, Honde Valley, Zimbabwe, use and interact with wetlands. The study also assessed the specific problems encountered by farmers in using wetlands for agriculture. Snowball and purposive sampling strategies were used to select participants for individual interviews and focus group discussions. Ethnographic techniques, such as participant observations and participatory action research, were also used to collect data. These were complemented with photos and direct observations of the physical characteristics of the six wetlands, and how people were using these wetlands. Semi-structured interviews and focus group discussions were conducted with farmers, the village heads, Agritex officers, seed companies and an Environmental Management Agency (EMA) official. Results show that wetland users depend on the valley bottom wetlands for provisioning and cultural services, and there are some changes between the ways in which wetlands have been used in the past compared to the present. Some of these changes included different types of crops grown on the wetlands and an increase in the amount of land used for wetland farming. As the wetlands were exploited mainly for provisioning services, some ecosystem supporting and regulatory services were affected. However, the changes reported by the farmers on different wetland elements such as the decrease in plant and animal species, loss of soil fertility and decrease in wetland water reflect how exploitation of some services has compromised other services. Therefore, the preservation of ecological characteristics and hydrological processes of the wetlands is threatened. The study also revealed that wetland farmers interacted with different stakeholders in different ways – with other wetland farmers when sharing ideas and seeds; village heads during wetland laws implementation; seed companies during seed breeding and seed selling; EMA officials during wetland restoration and implementation of wetland laws; and with Agritex officers when being shown good agronomy practises. In using wetlands for agriculture, farmers encountered challenges such as pests and diseases, stealing of crops, and water shortage in some parts of the wetlands. Although farmers were trying to employ sustainable methods of wetland exploitation, most of these methods were not correctly used. Training on conservation wetland farming was limited, hence farmers inappropriately employed dryland conservation farming techniques on wetland areas. Wetland users were not getting enough information from the EMA on wetland sustainable wetland use and management. Lack of collaboration amongst stakeholders involved in wetland use and management has compromised the sustainability of wetlands. The study contributes in advancing knowledge on how wetland use, methods of wetland exploitation, and different environmental attitudes by wetland users can affect the integrity and sustainability of the wetland ecosystem and sustainable development in a developing world context. This study recommends that the Ministry of Lands, Agriculture, Water, Climate and Rural Resettlement in Zimbabwe, through the Department of Agricultural Technical and Extension Services and the EMA, should ensure wise use of wetlands by equipping wetland farmers with wetland conservation farming skills and ensuring effective monitoring and implementing of wetlands laws
A thesis submitted to the School of Geography, Archaeology & Environmental Studies, Faculty of Science, University of The Witwatersrand, Johannesburg, in fulfilment of the degree of Doctor of Philosophy (in Geography and Environmental Studies), 2021